Baseline Evaluation With a Sweating Thermal Manikin of Personal Protective Ensembles Recommended for Use in West Africa. (28th August 2015) - Coca, Aitor; DiLeo, Travis; Kim, Jung-Hyun; Roberge, Raymond; Shaffer, Ronald
Abstract: Objective: Experience with the use of personal protective equipment (PPE) ensembles by health care workers responding to the Ebola outbreak in the hot, humid conditions of West Africa has prompted reports of significant issues with heat stress that has resulted in shortened work periods. Methods: A sweating thermal manikin was used to ascertain the time to achievement of a critical core temperature of 39°C while wearing 4 different PPE ensembles similar to those recommended by the World Health Organization and Médecins Sans Frontières (Doctors Without Borders) at 2 different ambient conditions (32°C/92% relative humidity and 26°C/80% relative humidity) compared with a control ensemble. Results: PPE ensembles that utilized coveralls with moderate to high degrees of impermeability attained the critical core temperature in significantly shorter times than did other ensembles. Encapsulation of the head and neck region resulted in higher model-predicted subjective impressions of heat sensation. Conclusions: To maximize work capacity and to protect health care workers in the challenging ambient conditions of West Africa, consideration should be given to adjustment of work and rest schedules, improvement of PPE (e.g., using less impermeable and more breathable fabrics that provide the same protection), and the possible use of cooling devices worn simultaneously with PPE. ( Disaster Med Public Health Preparedness . 2015;9:536–542)